Investigating the effect of 4-week fish oil supplementation on inflammation and plasma nitric oxide and reactive oxygen species in response to exhaustive exercise - Roya Zekri kondalaji; Vahid Sarisarraf; Maryam Nourshahi (Shahid Beheshti University, 2020)
Purpose: Previous studies in the case of fish oil showed its effectiveness on reducing inflammation and improving performance, but its effects on peripheral fatigue and related mediators are not well understood. Methods: 20 healthy men students (age: 26.90±2.64 yrs, weight: 78.33±10.42 kg, height: 175.80±4.89 cm, body fat percent: 18.40±5.46) were selected and randomly assigned into corn oil and fish oil groups and consumed daily doses of 6 gr for 4-weeks. Before and after supplementation, participants performed Bruce exhausting protocol and blood samples were taken before, immediately after and after 20-min recovery. Results: Our results showed significant decrease in baseline values of TNF-α and significant increase in baseline values of NO (P<0.05) after supplementation. In addition, three were significant differences between groups after supplementation in changes of TNF-α after recovery (F=7.38, P=0.015) and changes of NO after exercise (F=5.64, P=0.034) and recovery (F=8.83, P=0.011). However, no changes observed in the case of ROS. Conclusion: These results showed that fish oil supplementation could reduce baseline inflammation and thus, increase baseline NO that can improve anti-oxidant capacity. However, TNF-α response to recovery increased that seems to be highly affected by increase in post-supplementation baseline. In addition, NO responses to exercise decreased that is may be because of the lower physiological stress of activity.